Madres y micro-influencers: un nuevo perfil para las marcas en Instagram - Fernández-Gómez, Erika (2024)
Influencer marketing has become a fundamental tool in advertising. At the same time, the presence of minors on social media has become widespread, especially on their parents’ channels, as seen with micro-influencer mothers (those with less than 100 000 followers). This study aims to understand their communication and engagement strategies through an exploratory data analysis of the Instagram activity of five micro-influencers during five months (August to December 2022), analyzing 276 posts. The research shows that, like instamoms, the profiles studied feature several brands employing different advertising techniques, often lacking transparency regarding their commercial relationships. Most posts that showcase brands do not include any disclosure about a commercial collaboration. Fashion brands appear more frequently, but the food sector is particularly concerning, as many promote unhealthy products. Minors play an essential role by appearing in the most-liked and commercial posts. The results highlight the involvement of minors in profiles that fail to comply with key industry regulations, despite a great deal of advertising activity occurs, along with a lack of transparency from both micro-influencers and brands.